Determination of Sex in Ungulate Herbivores via near Infrared Spectroscopy of Hair: Growing Cattle as a Surrogate Model - Tolleson, Doug R (Journal of animal science, 2021)
Abstract Near infrared spectroscopy (NIRS) has been used in a variety of medical and veterinary science applications. In particular, NIRS calibrations have been developed in livestock for steroid content in cattle hair, and wound age or stage of healing in hot iron cattle brands. These NIRS applications also have potential utility in forensic science. Portable NIRS instruments facilitate measurements on live animals and or animal samples in the field. The objective of this study was to evaluate the efficacy of determining sex in growing cattle via NIRS of hair utilizing a portable spectrometer. In two consecutive years, log 1/R spectra (350–2500 nm) were collected using an ASD Field Spec fitted with a contact probe. Experimental subjects were Bos taurus cross calves (n = 12, yr 1; n = 14, yr 2) born to cows grazing central Arizona rangeland. Calf age was approximately 60, 90 and 210 d at branding, estrus synchronization, and weaning, respectively. As cattle were gathered for these routine working events, a total of 7 M and 19 F calves were scanned 3 times each over the left ribcage. A linear discriminant function was applied to spectral data in order to determine sample membership in M or F groups at each collection date. Chi-square procedures were used to determine differences (P < 0.05) in proportion of correct identifications per group and collection date. Overall, 86% of F and 72% of M were correctly (P < 0.05) identified. Corresponding values were 82% for F and 71% for M at branding, 100% for F and 89% for M at estrus synchronization, and 86% for F and 64% for M at weaning. Calf sex was successfully determined using portable NIRS in this proof of concept study. Efficacy of this method should be evaluated for different ungulate herbivores and under additional collection scenarios.